MODEL POLITIK ISLAM KULTURAL PADA ERA WALISONGO DALAM PEMBENTUKAN PERADABAN ISLAM NUSANTARA - Siti Mutomima; Machil Latul Chasanah; Amiruloh Amin; Anang Sholikhudin (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
Studies on the Walisongo era have predominantly focused on dakwah strategies and cultural acculturation, leaving a significant gap in understanding the systematic relationship between Islamic civilization-building and its political characteristics. This study aims to analyze the political model developed by Walisongo in shaping Islamic civilization in the Indonesian archipelago, with emphasis on the mechanisms of ulama-ruler relations, the political transformation from Hindu-Buddhist to Islamic systems, and the cultural-political integration that produced a distinctive Nusantara Islamic identity. Employing a qualitative historical method through systematic literature review of primary and secondary sources, this study finds that Walisongo constructed a culturally-grounded political model characterized by three core traits: accommodative legitimacy, adaptive governance, and integrative socio-political authority. Crucially, this model functioned not merely as a religious strategy but as a deliberate political architecture that enabled the Demak Sultanate and subsequent Islamic polities to consolidate power without coercive force. The novelty of this research lies in its analytical framework that bridges Islamic civilization theory (Ibn Khaldun), Islamization theory, and political Islam theory to explain the Walisongo political model as a coherent system—distinct from previous studies that treat these elements separately. This research contributes to the historiography of Islamic political thought in Southeast Asia and offers theoretical implications for understanding moderate Islam as a political heritage